Relationship Of Personal Hygiene by Nurses With Patient Satisfaction In Intensive Care Unit at Ciamis Hospital - Elis Roslianti; Aap Apipudin; Yuda Hendriyana; Ade Fitriani; Nur Hidayat (LPPM STIKes Muhammadiyah Ciamis, 2020)
The impact of patients who do not receive personal hygiene is that patients are susceptible to skin diseases, infectious diseases, and gastrointestinal diseases and there is a possibility that patients are exposed to nosocomial infections. As a result, patients are not satisfied and have a bad view of the quality of hospital services. Fulfillment of patient personal hygiene by nurses can lead to patient satisfaction which has an impact on good stigma in services. Patient dissatisfaction with hospital services can be caused by not getting basic services such as personal hygiene by nurses and only be charged to the family. As a result, the stigma of hospital services will be bad. Quantitative analytical research method using a cross-sectional approach. The number of samples was as many as 20 people with a sampling technique using an accidental sampling technique taken from ICU patients at Ciamis Hospital. The results of the research on the relationship of personal hygiene by nurses with patient satisfaction in the ICU room at Ciamis Hospital, the results of the Correlations statistical test showed a significant value of p-value = 0.000. personal hygiene by nurses in the ICU RSUD Ciamis obtained the highest frequency, namely the good category as many as 19 respondents (95%), and the lowest frequency, namely the unfavorable category, with as many as 1 respondent (5%). ICU patient satisfaction at RSUD Ciamis obtained the highest frequency, namely the satisfied category of 19 respondents (95%), and the lowest frequency was the dissatisfied category of 1 respondent (5%). Conclusion Based on the results of the Correlations statistical test, it showed a significant value of p-value = 0.000. So it can be concluded that there is a relationship between the personal hygiene of nurses on patient satisfaction.